TETRAHYDROCURCUMIN AND CHLOROGENIC ACID AGAINST STREP TOZOTOCIN–NICOTINAMIDE GENERATED OXIDATIVE STRESS-INDUCED DIABETES - DR. FASEFAL PLIMAYESHU, FASEFAL PLIMAYESHU; KALEA AKILY (International Journal of Multidisciplinary Research and Studies, 2021)
The present study was undertaken to analyze the protective effect of tetra hydrocurcumin (THC) and chlorogenic acid (CGA) against streptozotocin (STZ)–nico-tinamide (NA)-induced type 2 diabetes in adult Wistar rats. Diabetes was induced in experimental rats weighing 180–220 g, by one intraperitoneal (i.p.) injection of STZ (45 mg/kg BW), 15 min after the (i.p.) administration of NA (110 mg/kg BW). THC (80 mg/kg BW) and CGA (5 mg/kg BW) were orally administered to diabetic rats for a period of 45 days. Fasting plasma glucose, glycosylated haemoglobin (HbA1C), thiobarbituric acid reactive substances (TBARS), and lipid hydroperoxides (LOOH) were significantly increased, whereas insulin, total haemoglobin (Hb), non-enzymic antioxidants (reduced glutathione (GSH), vitamin C, vitamin E, and ceruloplasmin) were decreased significantly in diabetic rats. Though the diabetic rats treated with THC and CGA individual exerts beneficial effects altogether the biochemical parameters in (STZ)-induced diabetic rats. The combined treatment with THC and CGA normalized all the above-mentioned biochemical parameters in STZ-induced diabetic rats. Normal pancreatic histological architecture in THC and CGA-treated diabetic rats revealed that these phytochemicals exert a better degree of protection when administered together than one treatment of individual compounds